2019
DOI: 10.35772/ghm.2019.01021
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir nephrotoxicity among Asians living with HIV: review of the literature

Abstract: Tenofovir disoproxil fumarate (TDF), prodrug of tenofovir (TFV), is one of the most widely used nucleotide reverse transcriptase inhibitors (NRTIs) for the treatment of HIV infection in resource-rich and resourcelimited settings with proven efficacy and safety, and also for the treatment of hepatitis B infections. However, TDF can cause renal proximal tubular dysfunction and also reduces estimated glomerular filtration rate (eGFR) more than other NRTIs. To date, TDF-associated renal dysfunction is generally re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…It is reasonable to expect that drugs targeting key human metabolic enzymes can be used to inhibit viral replication. Indeed, nucleoside and nucleotide analogs such as Tenofovir, Sofosbuvir or Ribavirin are already being used as antiviral drugs 6 8 . Pharmacological inhibition of either acetyl-CoA carboxylase (ACC) or fatty acid synthase (FASN) has also been shown to result in a strong reduction of viral titers in vaccinia infection 9 .…”
Section: Introductionmentioning
confidence: 99%
“…It is reasonable to expect that drugs targeting key human metabolic enzymes can be used to inhibit viral replication. Indeed, nucleoside and nucleotide analogs such as Tenofovir, Sofosbuvir or Ribavirin are already being used as antiviral drugs 6 8 . Pharmacological inhibition of either acetyl-CoA carboxylase (ACC) or fatty acid synthase (FASN) has also been shown to result in a strong reduction of viral titers in vaccinia infection 9 .…”
Section: Introductionmentioning
confidence: 99%
“…As an NRTI, TFV has achieved therapeutic success for the treatment of HIV-1 infection. TFV has recently been reported with an increased risk of nephrotoxicity [ 85 ] despite no Mito-Tox induction in 2D cultures of HepG2 cells, human skeletal muscle cells, and renal proximal tubule epithelial cells [ 32 ], compared with other NRTIs. Another study showed that TFV achieves this independent of mtDNA depletion in HepG2 cell lines [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Viral diseases can be as benign as Therefore, drugs targeting key human metabolic enzymes can be used to inhibit viral replication. For example, nucleoside and nucleotide analogs such as Tenofovir, Sofosbuvir or Ribavirin are often used as antiviral drugs (Nishijima et al, 2019). Although the search for antivirals began with the successful isolation of small molecule-based compounds from microorganisms, such as certain antibiotics, almost all of the antiviral drug therapies currently in use are of chemical origin (Holmes et al, 1981;Velásquez et al, 2024).…”
Section: Antiviralsmentioning
confidence: 99%